Measuring the emotional response to beer and the relative impact of sensory and packaging cues - Chaya, C.; Pacoud, J.; Ng, May Ling; Fenton, A.; Hort, Joanne (American Society of Brewing Chemists, 2015)
In today’s extremely competitive markets, recent studies have highlighted that using hedonic measurement alone is inadequate for evaluating consumer product experience. Measuring emotional response is suggested to provide a richer insight into consumer responses. The objectives of this study were to: (i) measure consumer emotional responses to beer; (ii) determine if a relationship exists between sensory and emotional attributes of products; and finally (iii) investigate the relative impact of sensory and packaging attributes on the emotional response in beer. Using the EsSense Profile technique, level of liking and emotional response to a broad range of 10 commercial lager beers was evaluated by 90 lager consumers under three different conditions: blind (liquid only), pack (packaging only) and informed (liquid plus packaging). Emotional response was shown to discriminate across the beer samples in terms of both pleasantness and engagement level. Packaging cues were more influential on emotional response but sensory attributes did play a role. Increasing carbonation and familiarity, and decreasing sweetness and alcohol content were shown to influence a more pleasant and engaging emotional response in this set of beers. This study highlights the need to evaluate both liquid and packaging characteristics to gain better insights into developing and understanding the emotional signature of beer.